The Dietary Quality of Persons with Heart Failure in NHANES 1999–2006 - Lemon, Stephenie C. (Springer-Verlag, 2009)
BACKGROUND: Dietary quality may impact heart failure outcomes. However, the current status of the dietary quality of persons with heart failure has not been previously reported. OBJECTIVE: To describe sodium intake, patient factors associated with sodium intake and overall dietary quality in a national sample of persons with heart failure. DESIGN: Analysis of repeated cross-sectional probability sample surveys using data from National Health and Nutrition Examination Surveys (NHANES) of 1999–2000, 2001–2002, 2003–2004 and 2005–2006. PARTICIPANTS: The study sample consisted of 574 persons with self-reported heart failure (mean age = 70 years; 52% women). MEASUREMENTS: Diet of each survey participant was assessed using single 24 hour recall. Dietary nutrients of interest included sodium, the mainstay of heart failure dietary recommendations, and additionally potassium, calcium, magnesium, fish oils, saturated fat and fiber. Specific dietary goals were based on established guidelines. RESULTS: Mean sodium intake was 2,719 mg, with 34% consuming less than 2,000 mg per day. Patient factors associated with greater sodium intake included male gender, lower education, lower income and no reported diagnosis of hypertension. Mean potassium intake was 2,367 mg/day, with no differences by type of diuretic used or renal disease status. Adherence rates to established guidelines for other nutrients were 13% for calcium, 10% for magnesium, 2% for fish oils, 13% for saturated fat and 4% for fiber. CONCLUSIONS: Dietary quality of persons with self-reported heart failure was poor. Public health approaches and clinical dietary interventions are needed for persons with this increasingly prevalent clinical syndrome.